2017
DOI: 10.1371/journal.pone.0185595
|View full text |Cite
|
Sign up to set email alerts
|

De novo transcriptome sequencing and assembly from apomictic and sexual Eragrostis curvula genotypes

Abstract: A long-standing goal in plant breeding has been the ability to confer apomixis to agriculturally relevant species, which would require a deeper comprehension of the molecular basis of apomictic regulatory mechanisms. Eragrostis curvula (Schrad.) Nees is a perennial grass that includes both sexual and apomictic cytotypes. The availability of a reference transcriptome for this species would constitute a very important tool toward the identification of genes controlling key steps of the apomictic pathway. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(54 citation statements)
references
References 52 publications
(60 reference statements)
2
51
1
Order By: Relevance
“…This discrepancy might potentially be explained by master regulators which control complex programs of gene activity. Transcriptional analyses to identify genes differentially expressed in sexual as compared to apomictic plants have been presented for a variety of species including Pennisetum ciliare and Pennisetum glaucum [83,84], Panicum maximum [85,86], Poa pratensis [87,88], Brachiaria brizantha [89,90], Paspalum notatum and Paspalum simplex [91][92][93][94], Eragostris curvula [95], Medicago falcata [96], Boehmeria tricuspis [97], Hypericum perforatum [62,98], Hieracium [99,100], Boechera [101][102][103], and also for Citrus [76] ( Table 2). These studies provide evidence for temporal deregulation of the gene regulatory processes governing sexual reproduction in apomicts and identify large numbers of up to hundreds of genes to be differentially expressed.…”
Section: Transcriptional Analysis Identifies Genes Differentially Regmentioning
confidence: 99%
“…This discrepancy might potentially be explained by master regulators which control complex programs of gene activity. Transcriptional analyses to identify genes differentially expressed in sexual as compared to apomictic plants have been presented for a variety of species including Pennisetum ciliare and Pennisetum glaucum [83,84], Panicum maximum [85,86], Poa pratensis [87,88], Brachiaria brizantha [89,90], Paspalum notatum and Paspalum simplex [91][92][93][94], Eragostris curvula [95], Medicago falcata [96], Boehmeria tricuspis [97], Hypericum perforatum [62,98], Hieracium [99,100], Boechera [101][102][103], and also for Citrus [76] ( Table 2). These studies provide evidence for temporal deregulation of the gene regulatory processes governing sexual reproduction in apomicts and identify large numbers of up to hundreds of genes to be differentially expressed.…”
Section: Transcriptional Analysis Identifies Genes Differentially Regmentioning
confidence: 99%
“…Eragrostis curvula (weeping lovegrass), an African grass with cytotypes of different ploidy levels (e.g., 2x–8x) and displaying obligate and facultative apomixis and sexual reproduction [ 46 ], has become a model for the analysis of apomixis mechanisms, due to its particular diplosporous development (meiotic diplospory maintaining the same embryo: endosperm ploidy ratio as in sexual seeds). In recent years, the reproductive mode of this grass was studied extensively, providing information about the cytoembryological aspects of its apomictic–sexual development [ 47 ], differentially expressed (DE) transcripts [ 48 , 49 , 50 , 51 ], epigenetic aspects of apomictic regulation [ 52 , 53 ], mapping of the apomixis locus [ 54 ] and a high quality genome assembly [ 55 ]. Our group also demonstrated that under different internal and external stressful situations, including a change in ploidy, water stress, in vitro culture and intraspecific hybridization, the number of sexual embryo sacs increased in facultative apomictic plants of this grass [ 40 , 56 ].…”
Section: Introductionmentioning
confidence: 99%
“…The aim of the present study was to identify genes that are differentially expressed in weeping lovegrass inflorescences of control and water-stressed facultative apomictic plants and to compare them with the differentially expressed genes between apomictic and sexual plants previously reported by our group [ 51 ]. This approach was taken based on previous findings about increases of sexual processes under stress conditions [ 40 ], in order to look for common pathways between stress and apomixis.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to identify components of apomixis by transcriptional profiling of reproductive organs using Differential Display PCR (DD-PCR), SuperSAGE (serial analysis of gene expression), and high-throughput sequencing on microdissected ovules revealed 1) differentially expressed genes in reproductive tissues of apomictic and sexual relatives from different plant systems (e.g., Pennisetum, [69,70]; Brachiaria, [71,72]; Panicum, [73,74]; Poa, [75], Eragrostis, [76][77][78]; Paspalum, [42,64,[79][80][81]; Hieracium, [82,83]; Hypericum [84,85]) and 2) an overall shift in gene regulation at the MMC stage and a global heterochronic gene expression between the sexual and apomeiotic ovules (e.g., Boechera, [86][87][88][89]; Paspalum [79,90,91]; Pennisetum, [92]; Hieracium, [83,93,94]; Hypericum [85,95]; Ranunculus [96,97]). Such wide-ranging de-regulation on gene expression levels between sexual and apomictic ovules affect genes encoding varied biological functions (GO classes) and regulatory pathways, including key genes of the sexual pathway, RNA-directed DNA methylation and transcription regulation, hormonal signaling, and cell cycle control (see details in the next section).…”
Section: Genetic and Genomic Features Of Apomixismentioning
confidence: 99%